The Principle of Contrarius Actus in the Dispute Over the Appointment of the Acting Regent of Padang Lawas Regency - Andrew Amanah Carnegie Hasibuan; Irwansyah Irwansyah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
This research discusses the Principle of Contrarius Actus in the Appointment Dispute for the Regent of Padang Lawas. This research uses the observation method. The observation method is a process of observing the five senses, interviews are to get answers by asking questions and answers, documentation is past notes and literature study is collecting the required documents. The research approach used is an empirical juridical approach aimed at obtaining primary data and secondary data through field research and library research. Researchers obtain sources through literature studies in the form of articles, journals, document studies in the form of photographs and field studies by means of interviews and observations. In the discussion, we know a lot that the New Order government and regions could not develop optimally because the political and economic system built by the New Order government was very centralized. On November 24 2021, a problem arose between the regent and the deputy regent of Padang Lawas regarding the issuance of a letter issued by the Governor of North Sumatra number 132/12201/2021 regarding the deputy regent of Padang Lawas as acting Regent of Padang Lawas, where the contents of the letter lacked careful consideration and it seemed like they were in a hurry, proven by the fact that the regent's health was not checked. The publication of the letter issued by the Governor of North Sumatra resulted in the regent no longer being able to carry out his duties, authority and functions as Regent of Padang Lawas comprehensively. The occurrence of a conflict between the Regent and Deputy Regent of Padang Lawas resulted in the loss of rights and obligations in carrying out their duties and authority as regent.